Pengembangan penanda molekuler untuk deteksi Phytophthora palmivora pada tanaman kakao Development of molecular marker for the detection of Phytophthora palmivora in cacao - T W DARMONO; Ilyas JAMIL; Dwi Andreas SANTOSA (E-Journal Menara Perkebunan, 2006)
Summary Pod rot is one of the most important diseases in cacao. This disease could be incited by Phytophthora palmivora, P. megakarya,  P. capsici or P. citrophthora.  The causal agent of pod rot disease in cacao in Indonesia is known to be P. palmivora.  The success of pod rot disease management is partly depend on the success of efforts in reducing the quantity and quality of the disease inoculum above and below soil surface.  Provision of molecular-based detection system would improve the accuracy of determination of these two parameters. The objective of this experiment was to develop a pair of primers that could be used to specifically amplify rDNA fragments of P. palmivora associated with pod rot disease in cacao.  Design of these primers was made based on the DNA sequence of rDNA fragment amplified using a pair of universal primers ITS4/ITS5. Regions showing high degree of dissimilarity among species of Phytophthora and high degree of similarity within the same species of P. palmivora were determined through DNA alignment.  Specific forward primer (DTF) 5¢-CTT AGT TGG GGG TCT CTT TC-3¢  and reverse primer (Ilyas1R) 5¢-GTT CAC CAA TCA TAC CAC C-3¢ were obtained. This pair of primers had been proven to specifically amplify only rDNA fragment, approximately 650 bp, of P. palmivora associated with pod rot disease and stem canker in cacao.Ringkasan Penyakit busuk buah merupakan salah satu penyakit terpenting pada tanaman kakao.  Penyakit ini dapat disebabkan oleh Phytoph-thora palmivora, P. megakarya, P. capsici atau P. citrophthora. Di Indonesia busuk buah disebabkan oleh P. palmivora. Keberhasilan pengendalian penyakit busuk buah salah satunya tergantung kepada keberhasilan penekanan kuantitas dan kualitas inokulum baik yang berada di atas maupun di bawah permukaan tanah. Tersedianya perangkat deteksi molekuler akan sangat membantu dalam upaya penetapan kedua parameter ter-sebut. Penelitian ini bertujuan untuk mengem-bangkan satu pasang primer yang secara spesifik mampu mengamplifikasi hanya fragmen rDNA P. palmivora yang berkaitan dengan busuk buah kakao. Desain primer dilakukan dengan mengacu kepada sekuen rDNA yang diamplifikasi dengan pasangan primer universal ITS4/ITS5. Daerah yang menunjukkan urutan basa dengan tingkat keragaman yang tinggi antar spesies Phytoph-thora dan yang menunjukkan tingkat kesamaan tinggi dalam satu spesies P. palmivora  yang sama  ditelusuri melalui penjajaran DNA. Hasil desain primer diperoleh primer forward (DTF) 5¢-CTT AGT TGG GGG TCT CTT TC-3¢  dan  reverse (Ilyas1R) 5¢-GTT CAC CAA TCA TAC CAC C-3¢. Pasangan primer DTF dan Ilyas1R ini hanya mampu mengamplifikasi fragmen rDNA berukuran 650 bp dari P. palmivora penyebab penyakit  buah  dan kanker batang kakao.